Correction: Nasri et al. A Novel Data-Driven Approach to Examine Children's Movements and Social Behaviour in Schoolyard Environments. Children 2022, 9, 1177 - Maedeh Nasri; Yung-Ting Tsou; Alexander Koutamanis; Mitra Baratchi; Sarah Giest; Dennis Reidsma; Carolien Rieffe (MDPI AG, 2022)
The authors request the following corrections because the changes made according to the second round of the review process were not included in the original publication [...]